2017
DOI: 10.1007/s41686-017-0002-4
|View full text |Cite
|
Sign up to set email alerts
|

Examination of an Innovative Solution for Internationalizing the Curriculum Through Online Study Abroad

Abstract: As we move further into the twenty-first century, businesses continue to seek employees with global experience and intercultural competence, but the reality is that many students are unable to gain this experience through study abroad programs for a variety of reasons. The purpose of this study was to determine if there is value in using web conferencing technology to provide students with access to international learning activities or ways to internationalize the curriculum for students who are unable to trav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…This formative case evaluation is the second in a series of iterative studies where the recommendations of the previous study are implemented and then evaluated. Based on Howard and Gunter's (2017) study with a global health management course in Brazil, the methodology was replicated in this study with the addition of a pre/post global citizenship assessment to address potential learning outcomes in a more formal class structure.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This formative case evaluation is the second in a series of iterative studies where the recommendations of the previous study are implemented and then evaluated. Based on Howard and Gunter's (2017) study with a global health management course in Brazil, the methodology was replicated in this study with the addition of a pre/post global citizenship assessment to address potential learning outcomes in a more formal class structure.…”
Section: Methodsmentioning
confidence: 99%
“…In a follow-up study that employed the same technology to broadcast from India, Kenny and Gunter (2015) found that the additional use of the text chat feature during the live broadcast appeared to increase student engagement and their sense of social presence. Howard and Gunter (2017) then initiated a series of formative case evaluations to develop a more cost-effective delivery mechanism for providing similar live broadcasts from the field with interactive chat. Advances in mobile technology now allow educators to take instruction outside of the classroom to facilitate learning in creative delivery methods with sound instructional strategies (Sung, Chang, & Liu, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations